Randomized Study of Persistent Atrial Fibrillation Ablation: Ablate in Sinus Rhythm Versus Ablate Complex-Fractionated Atrial Electrograms in Atrial Fibrillation. (February 2016) - Bassiouny, Mohamed; Saliba, Walid; Hussein, Ayman; Rickard, John; Diab, Mariam; Aman, Wahaj; Dresing, Thomas; Callahan, Thomas; Bhargava, Mandeep; Martin, David O.; Shao, Mingyuan; Baranowski, Bryan; et al.
Abstract : Background—: Achieving long-term successful outcomes with ablation of persistent atrial fibrillation (AF) remains a clinical and procedural challenge. We aimed to assess 2 ablation strategies for persistent AF: pulmonary vein antral isolation (PVAI) in sinus rhythm after direct current cardioversion versus PVAI and ablation targeting complex-fractionated atrial electrograms while in AF. Methods and Results—: Between June 2009 and July 2013, patients with continuous persistent AF for ≥3 months were prospectively randomized to either direct current cardioversion before PVAI and posterior wall/septum ablation while in sinus rhythm (group 1), versus same ablation in group 1 in addition to complex-fractionated atrial electrogram ablation while in AF (group 2). The procedural profiles and clinical outcomes of the 2 strategies were compared. Ninety patients were randomized to group 1 (n=46) or group 2 (n=44). There were no differences in baseline characteristics between groups. Over 365 days of follow-up after the index procedure, 16 patients (35%) in group 1 and 13 patients (30%) in group 2 remained arrhythmia-free off antiarrhythmic medications. Over long-term follow-up (median, 867 days), arrhythmia-free survival off antiarrhythmic medications was more likely in group 1 than in group 2 in Kaplan–Meier analysis (Log Rank P =0.04). Group 1 ablation was associated with significantly shorter procedural duration and fluoroscopy time (231±72 versus 273±76 min; P =0.008 and 54 [Q1–Q3: 46–67] versus 66 (Q1–Q3: 53–83] min; P =0.018, respectively). Conclusions—: In patients with persistent AF, PVAI in sinus rhythm after direct current cardioversion is associated with higher success and shorter procedural and fluoroscopy times compared with PVAI in AF with additional complex-fractionated atrial electrogram ablation. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02429648. Abstract : Supplemental Digital Content is available in the text.